2016
DOI: 10.1098/rstb.2015.0298
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial peptides and cell processes tracking endosymbiont dynamics

Abstract: One contribution of 13 to a theme issue 'Evolutionary ecology of arthropod antimicrobial peptides'. Many insects sustain long-term relationships with intracellular symbiotic bacteria that provide them with essential nutrients. Such endosymbiotic relationships likely emerged from ancestral infections of the host by free-living bacteria, the genomes of which experience drastic gene losses and rearrangements during the host-symbiont coevolution. While it is well documented that endosymbiont genome shrinkage resul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
50
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(55 citation statements)
references
References 76 publications
1
50
0
Order By: Relevance
“…Persistent associations between hosts and microbes are often not pathogenic; mutualists in insects, for example, establish persistent colonization of host organs and provide benefits to the hosts [6]. Such persistent associations by mutualists are maintained by AMPs [7].…”
Section: Introductionmentioning
confidence: 99%
“…Persistent associations between hosts and microbes are often not pathogenic; mutualists in insects, for example, establish persistent colonization of host organs and provide benefits to the hosts [6]. Such persistent associations by mutualists are maintained by AMPs [7].…”
Section: Introductionmentioning
confidence: 99%
“…Microbes entering the gut can potentially become pathogenic, but perhaps could also be considered as competitors for food (in the sense of Janzen's inter-kingdom competition between microbes and, in the original version, scavengers [90]). In many invertebrates, AMPs play an important role interacting with the gut microbiota [91] or co-evolved symbionts [10,92]. Studies in C. elegans have demonstrated that the combination of AMPs expressed in the gut differs from the composition of AMPs expressed on the exterior cuticle [56], which would add to the interaction scenario.…”
Section: Introductionmentioning
confidence: 99%
“…Last but not least, it is conceivable that antimicrobial effectors in C. elegans are also used to control the worm's microbiome, in analogy to what is known for example for weevils (see review by Masson et al [97]) and proposed for fruitflies (see review by Broderick [84]). At the same time, it is possible that members of the worm's microbial associates themselves produce protective antimicrobial factors, thus increasing the nematode's arsenal of effector molecules.…”
Section: Future Challenges: Functional Evidence For Worm Immune Effecmentioning
confidence: 99%